2016
DOI: 10.1007/s12520-016-0363-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation using cervical dental measurements in an archaeological population from Iran

Abstract: Sex estimation of skeletal remains is one of the major components of forensic identification of unknown individuals. Teeth are a potential source of information on sex and are often recovered in archaeological or forensic contexts due to their post-mortem longevity. Currently, there is limited data on dental sexual dimorphism of archaeological populations from Iran. This paper represents the first study to provide a dental sex estimation method for Iron Age populations. The current study was conducted on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
(92 reference statements)
10
21
0
Order By: Relevance
“…Teeth, as one of the strongest tissues in the human body, can be used for this purpose. Most studies on dental sexual dimorphism are based on crown and cervical mesiodistal and buccolingual diameters of teeth (Acharya & Mainali, 2007;Hassett, 2011;Viciano, Lopez-Lazaro, & Aleman, 2013;Kazzazi & Kranioti, 2016). These studies have shown that the canine is the most sexually dimorphic tooth, providing accuracy rates in this respect of over 85% (Hassett, 2011, Viciano, D'Anastasio, & Capasso, 2015Kazzazi & Kranioti, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teeth, as one of the strongest tissues in the human body, can be used for this purpose. Most studies on dental sexual dimorphism are based on crown and cervical mesiodistal and buccolingual diameters of teeth (Acharya & Mainali, 2007;Hassett, 2011;Viciano, Lopez-Lazaro, & Aleman, 2013;Kazzazi & Kranioti, 2016). These studies have shown that the canine is the most sexually dimorphic tooth, providing accuracy rates in this respect of over 85% (Hassett, 2011, Viciano, D'Anastasio, & Capasso, 2015Kazzazi & Kranioti, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are very few studies of sex prediction using odontometric data in either Iranian archaeological or modern populations. The only previous study was done by Kazzazi and Kranioti (2016) using cervical mesiodistal and buccolingual measurements for sex estimation in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…Dental sexual dimorphism has long been acknowledged as a reliable biological feature in this respect, and studies have demonstrated that dental dimensions can be used to accurately assess the sex of skeletal remains in different populations [1][2][3][4][5][17][18][19][20][21][22][23][24]. The present study is one of few reference studies for sex estimation using odontometric data in Iranian archaeological populations [7].…”
Section: Resultsmentioning
confidence: 85%
“…Since there are currently very few studies of sex estimation using odontometric data in either Iranian archaeological or modern populations the present study makes a significant contribution to the development of the standards of sex assessment in this population [7].…”
Section: Introductionmentioning
confidence: 99%
“…The aims of this study were (a) to assess the reliability, accuracy, and reproducibility of cervical mesiodistal and buccolingual measurements from virtual models created using CT scan images and (b) to compare them with the same measurements obtained using physical digital calipers on actual teeth. We used the digital calipers method as a standard, because the reliability and accuracy of this method has previously been tested (e.g., Kazzazi & Kranioti, ; Viciano, D'anastasio, & Capasso, ).…”
Section: Introductionmentioning
confidence: 99%